Milk proteins : from expression to food - Thompson, Abby; Boland, Mike, 1950-; Singh, Harjinder (Food science and technology international series., 2009)
In recent years, there has been a great deal of progress in the understanding and management of milk proteins across the production chain. This book takes a uniquely comprehensive look at those developments and presents them in a one-source overview. By providing a brief overview of each topic area, and then describing the most important recent advances therein, the "field-to-table" approach of this book provides specialists with new and directly relevant information in their own areas, along with information from complementary research fields, allowing them to contextualize their work within the larger pictures. At the same time it provides generalists with a complete overview and offers insights into topics for more in-depth reading. Covering areas that are receiving attention from people of many fields -- genomics, functional foods -- and including the latest research and developments in milk-protein phenomenon and interactions, this book will be an ideal resource for professionals and students alike. *A fresh look at recent developments across the entire production chain -- from animal genetics to nutritional and nutrigenomic needs of the customer. Up-to-date information from internationally-recognised authors from both academic and commercial resources.